The Effect of FATP1 on Adipocyte Differentiation in Qinchuan Beef Cattle - Xuchun Liu; Shijun Li; Liyun Wang; Weiyi Zhang; Yujuan Wang; Linsheng Gui; Linsen Zan; Chunping Zhao (Animals, 2021)
FATP1 plays an important role in the regulation of fatty acid metabolism and lipid accumulation. In this study, we investigated the patterns of FATP1 expression in various tissues obtained from calf and adult Qinchuan cattle, and in differentiating adipocytes. Next, we investigated the effect of FATP1 expression on preadipocyte differentiation in Qinchuan cattle using overexpression and interference assays. We also identified the differentially expressed genes (DEGs) and pathways associated with FATP1 overexpression/interference. Our results reveal that FATP1 was broadly expressed in heart, kidney, muscle, small intestine, large intestine, and perirenal fat tissues. While FATP1 overexpression promoted preadipocyte differentiation, fat deposition, and the expression of several genes involved in fat metabolism, FATP1 interference had the opposite effects on adipocyte differentiation. Following FATP1 overexpression and FATP1 interference in adipocytes, RNA-seq analysis was performed to identify DEGs related to fat metabolism. The DEGs identified include SLPI, STC1, SEMA6A, TNFRSF19, SLN, PTGS2, ADCYP1, FADS2, and SCD. Pathway analysis revealed that the DEGs were enriched in the PPAR signaling pathway, AMPK signal pathway, and Insulin signaling pathway. Our results provide an in-depth understanding of the function and regulation mechanism of FAPT1 in fat metabolism.